Contracting as a bridging factor linking outer and inner contexts during EBP implementation and sustainment: a prospective study across multiple U.S. public sector service systems - Lengnick-Hall, Rebecca (Implement Sci, 2020)
BACKGROUND: Bridging factors are relational ties (e.g. partnerships), formal arrangements (e.g. contracts or polices) and processes (e.g. data sharing agreements) linking outer and inner contexts and are a recent evolution of the Exploration-Preparation-Implementation-Sustainment (EPIS) framework. Bridging factor research can elucidate ways that service systems may influence and/or be influenced by organizations providing health services. This study used the EPIS framework and open systems and resource dependence theoretical approaches to examine contracting arrangements in U.S. public sector systems. Contracting arrangements function as bridging factors through which systems communicate, interact, and exchange resources with the organizations operating within them. METHODS: The sample included 17 community-based organizations in eight service systems. Longitudinal data is derived from 113 contract documents and 88 qualitative interviews and focus groups involving system and organizational stakeholders. Analyses consisted of a document review using content analysis and focused coding of transcripts from the interviews and focus groups. A multiple case study analysis was conducted to identify patterns across service systems and organizations. The dataset represented service systems that had sustained the same EBP for between 2 and 10 years, which allowed for observation of bridging factors and outer-inner context interactions over time. RESULTS: Service systems and organizations influenced each other in a number of ways through contracting arrangements. Service systems influenced organizations when contracting arrangements resulted in changes to organizational functioning, required organizational responses to insufficient funding, and altered interorganizational network relationships. Organizations influenced service systems when contract arrangements prompted organization-driven contract negotiation/tailoring, changes to system-level processes, and interorganizational collaboration. Service systems and organizations were dependent on each other as implementation progressed. Resources beyond funding emerged, including adequate numbers of eligible clients, expertise in the evidence-based practice, and training and coaching capacity. CONCLUSION: This study advances implementation science by expanding the range and definition of bridging factors and illustrating specific bi-directional influences between outer context service systems and inner context organizations. This study also identifies bi-directional dependencies over the course of implementation and sustainment. An analysis of influence, dependencies, and resources exchanged through bridging factors has direct implications for selecting and tailoring implementation strategies, especially those that require system-level coordination and change.